Bay‐annulated indigo based near‐infrared sensitive polymer for organic solar cells. Issue 2 (4th November 2017) - Zhu, Jingshuai; Li, Tengfei; Shi, Keli; Wang, Jiayu; Lin, Yuze; Yu, Gui; Zhan, Xiaowei
ABSTRACT: A new conjugated polymer (PBAIIDTT) based on bay‐annulated indigo and indacenodithieno[3, 2‐ b ]thiophene was designed, synthesized, and characterized. PBAIIDTT shows strong absorption in 400–500 and 600–800 nm, and its HOMO and LUMO energy levels are −5.45 eV and −3.65 eV, respectively. In organic field‐effect transistors, the polymer exhibits a relatively high hole mobility of 0.39 cm 2 V −1 s −1 . PBAIIDTT was added to poly(3‐hexylthiophene) (P3HT) and phenyl‐C61 ‐butyric acid methyl ester (PC61 BM) based organic solar cells. Ternary blend solar cells with 10% PBAIIDTT show an increased short circuit current density due to the broadened photocurrent generated in the near‐infrared region, and a power conversion efficiency of 3.78%, which is higher than that of the P3HT:PC61 BM binary control devices (3.33%). © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 213–220 Abstract : A new conjugated polymer (PBAIIDTT) based on bay‐annulated indigo and indacenodithieno[3, 2‐ b ]thiophene was designed, synthesized, and characterized. PBAIIDTT exhibits a hole mobility of 0.39 cm 2 V −1 s −1 in field‐effect transistors. Organic solar cells based on a P3HT:PC61 BM:PBAIIDTT ternary blend show efficiency of 3.78%, which is higher than that of the P3HT:PC61 BM binary control devices (3.33%).